Correlates of habitual physical activity and organized sports in German primary school children. Issue 3 (March 2015) - Kobel, S.; Kettner, S.; Kesztyüs, D.; Erkelenz, N.; Drenowatz, C.; Steinacker, J.M.
Abstract: Objectives: The increased prevalence of childhood obesity has also been attributed to low physical activity (PA) levels. Understanding factors affecting child PA levels is especially important considering the benefits PA offers to youth. Study design: This study therefore examined different correlates affecting habitual PA and sports participation in primary school children. Methods: Height and weight were measured during a school visit in 1714 children (7.1 ± .6 years). PA and behavioural correlates were assessed by parental questionnaire. The effect of various correlates on PA as well as participation in organized sports was assessed using logistic regression analysis. Results: Significant correlates of PA and sports participation were engagement in sporting activities outside of clubs and children's weight status. Playing outdoors for more than 60 min/day was significant for PA, having well educated parents and being male. Participation in sports was influenced by children's media consumption, active travel to school and having active parents. No influence was found for migration, income, parental weight status and health consciousness. Conclusion: In this study, a multiplicity of independent correlates of PA and sports participation, which require a broad approach to promote an active lifestyle, have been considered. Understanding these factors might support the development of effective health-promoting interventions. Highlights: Correlates affecting habitual PA and sports participation in children were examined. Outdoor play, gender, and parental education are associated with habitual PA. Body weight is negatively associated with organised sports. Higher body weight increased the odds of higher physical activity. Parental PA has a strong impact on children's participation in organised sports.